Application of flow cytometry to analyze microbial quality of dental unit waterWhy Is This important? - Clifton M. Carey, PhD; Shannon E. Mills, DDS; Richard Vigil, MS; Madison Aungst, BS, DDS; Lacey Favazzo, PhD (JADA Foundational Science)
Background: Dental unit waterline (DUWL) safety is vital for dental practitioners. Unfortunately, the standard heterotrophic plate count (HPC) methods commonly used to identify bacterial contamination dramatically underestimate planktonic bacteria counts. Flow cytometry (FCM) directly counts bacterial cells using laser-activated fluorescence, providing more reliable and timely results. Methods: Approximately 1,700 DUWL samples were measured by both HPC and FCM methods. HPC samples were plated on R2A agar within 8 hours of receipt, incubated at 25 °C for 7 days, and reported as colony-forming units (CFU)/mL. FCM samples were treated with SYBR Green I fluorescent stain, analyzed and reported as high nucleic acid (HNA) and low nucleic acid (LNA) cell counts. An empirical algorithm was developed using HNA and LNA cell counts compared with the recommended action limit for the Centers for Disease Control and Prevention’s greater than 500 CFU/mL pass or fail. Results: An FCM threshold limit that included both HNA 250 or greater and LNA 750 or greater cell counts was derived by pairing FCM data with R2A samples dichotomized as passing (≤ 500 CFU/mL) or failing (> 500 CFU/mL) to establish corresponding pass or fail criteria that would minimize false pass and false fail compared with R2A results. 1,388 (81.6%) of samples passed the R2A limit of 500 CFU/mL or fewer, whereas 1,427 (83.9%) FCM samples passed the proposed HNA 250 or fewer and LNA 750 or fewer criteria. Conclusions: The data show that FCM analysis and the proposed threshold criteria can be used as a powerful adjunctive tool for monitoring DUWL contamination, which includes greater accuracy and the ability to analyze samples immediately on receipt.